International responses to mass atrocities in Africa : responsibility to protect, prosecute, and palliate - Mills, Kurt (Pennsylvania studies in human rights., 2015)
In International Responses to Mass Atrocities in Africa, Kurt Mills develops a typology of responses to mass atrocities, investigates the limitations of these responses, and calls for such responses to be implemented in a more timely and thoughtful manner.